2021
DOI: 10.1093/ckj/sfab030
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation and COVID-19 renal and patient prognosis

Abstract: Coronavirus disease 2019 (COVD-19) emerged as a pandemic in December 2019. Infection has spread quickly and renal transplant recipients receiving chronic immunosuppression have been considered a population at high risk of infection, complications and infection-related death. During this year a large amount of information from nationwide registries, multicentre and single-centre studies have been reported. The number of renal transplant patients diagnosed with COVID-19 was higher than in the general population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 94 publications
0
38
0
3
Order By: Relevance
“…The variation in CFR might associate with the relatively low national COVID-19 prevalence in China of the Western Pacific region compared to other included countries [ 3 ]. There was no difference in CFR among different RRT modalities which might relate to the lack of association of COVID-19 mortality and immunosuppression regimen [ 66 ], and surrogates in kidney transplant patients [ 67 ]. Subgroup analysis provided a 14.87% case fatality rate in HD patients which was lower than the 25.7% case fatality rate in HD patients from another meta-analysis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variation in CFR might associate with the relatively low national COVID-19 prevalence in China of the Western Pacific region compared to other included countries [ 3 ]. There was no difference in CFR among different RRT modalities which might relate to the lack of association of COVID-19 mortality and immunosuppression regimen [ 66 ], and surrogates in kidney transplant patients [ 67 ]. Subgroup analysis provided a 14.87% case fatality rate in HD patients which was lower than the 25.7% case fatality rate in HD patients from another meta-analysis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that patients with acute renal injury have a higher mortality rate. ACE2 is strongly expressed in the kidneys (Mizuiri & Ohashi, 2015 ; Toapanta et al, 2021 ). A decrease in ACE2 and an enhancement in ACE expression might eventually lead to renal damage in diabetes (Mizuiri & Ohashi, 2015 ).…”
Section: Natural Compounds For Organs Protectionmentioning
confidence: 99%
“…Renal transplant patients with COVID-19 age nearly 60, and two-third of them are males. Comorbidities reflect patients' age (diabetes, hypertension, cardiovascular and pulmonary diseases) and are frequently serious being transplanted subjects under immunosuppressive therapy to prevent rejection [50,[62][63][64][82][83][84][85]; this frequently leads COVID-19 toward a severe course [85].…”
Section: Covid-19 In Kidney Transplant Patientsmentioning
confidence: 99%